Streetcar accidents in built-up areas. Accident occurrence and measures for improving safety. - Bakaba, Jean Emmanuel; Ortlepp, Jörg (Trialog Publishers, 2018)
Around 4.100 streetcar accidents with personal injury in 58 German cities in a three-years-period were analyzed. Pedestrians make up by far the largest share of fatalities and cases of serious injury. Cyclists also feature disproportionately strongly in accidents involving serious injury. Pedestrians suffer serious accidents disproportionately often on stretches of road and at streetcar stops. Streetcars themselves are main responsible in only 15.7 percent of the analyzed accidents. Serious accidents occur, in particular, at signal-controlled intersections and on three- or four-lane roads with a separate streetcar track bed in the middle.
Keywords: Öffentlicher Verkehr; Stadtverkehr; Straßenbahn; Gleis; Verkehrsunfall; Unfallursache; Verkehrssicherheit; Straßenkreuzung; Trasse; Gleisanlage; Unfallstatistik